Microglia isolation from aging mice for cell culture: A beginner’s guide - Vijaya, Akshay Kumar; Iešmantaitė, Monika; Mela, Virginia; Baltriukienė, Daiva; Burokas, Aurelijus (Frontiers in Cellular Neuroscience, 2023)
Microglia are the innate immune cells of the central nervous system that play a critical role in neuroinflammation. Although numerous methods have been developed to isolate microglia from embryonic or postnatal mouse brains, still major difficulties exist in isolating microglia from adult mice, often resulting in low yield and risk of cellular activation. Therefore, there is a need for a more efficient method to isolate pure and high-yield microglia from adult mice to study various neurodegenerative diseases. The aim of this study was to develop a fully functional protocol for the isolation of microglia by comparing different protocols. We investigated the efficacy of three protocols in terms of cell yield, purity, cellular activation, cellular aging, and migration properties and proposed the modified protocol (PROTOCOL 1), which provides an optimal yield of functional microglial cells with a minimum of material and equipment, and allows young researchers with little experience to isolate microglia and helps them to delve deeper into the world of neuroscience.